2011
DOI: 10.1016/j.jfi.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Competition and relationship lending: Friends or foes?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 78 publications
5
44
0
Order By: Relevance
“…A difference-in-difference estimation shows that firms located closer to the Austrian border are more likely to perceive bank access to loans as accommodating as long as regulatory differences exist. This result is consistent with the research of Presbitero and Zazzaro (2011), who find that more competition (in our case, through regulatory differences) increases relationship lending in markets dominated by small local banks.…”
supporting
confidence: 93%
“…A difference-in-difference estimation shows that firms located closer to the Austrian border are more likely to perceive bank access to loans as accommodating as long as regulatory differences exist. This result is consistent with the research of Presbitero and Zazzaro (2011), who find that more competition (in our case, through regulatory differences) increases relationship lending in markets dominated by small local banks.…”
supporting
confidence: 93%
“…Their results show that competition and close banking relationships are not necessarily hostile. Presbitero and Zazzaro [22] explain this non-monotonic relationship by the structure of the local credit market. They found that a marginal increase in interbank competition is crucial for relational financing in markets characterized by the presence of large banks and foreign banks.…”
Section: Interbank Competition and Benefits Of Relational Fundingmentioning
confidence: 99%
“…HERFINDAHL is calculated based on the share of banks' branches within the prefecture in which a borrowing firm is located. BK_SHARE and HERFINDAHL may also be important for firm-bank relationships, although the existing empirical literature is ambiguous on whether market concentration (competition) is conducive or detrimental to relationship lending (Elsas, 2005;Ongena, 2007, Presbitero andZazzaro, 2011). …”
Section: Other Control Variablesmentioning
confidence: 99%